2016
DOI: 10.4491/eer.2016.120
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vacuum regeneration of activated carbon on volatile organic compound adsorption

Abstract: Vacuum swing adsorption (VSA) is a promising treatment method for volatile organic compounds (VOCs). This study focuses on a VSA process for regenerating activated carbon spent with VOCs, and then investigates its adsorption capacities. Toluene was selected as the test VOC molecule, and the VSA regeneration experiments results were compared to the thermal swing adsorption process. Cyclic adsorption-desorption experiments were performed using a lab-scale apparatus with commercial activated carbon (Samchully Co.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 16 publications
(18 reference statements)
2
6
0
Order By: Relevance
“…Therefore, the results demonstrated that ACF 2 outperformed ACF 1 and showed comparatively higher adsorption efficiency than ACF 3 . Similar results were derived in a previous study on cellulose-based ACFs modified by an amine functional group for the adsorption of acetaldehyde under 40% humidity conditions [32]. At start acetaldehyde adsorbed physically onto the active sites with oxygen and nitrogen of adsorbent that creates a bonding with acetaldehyde molecule quickly.…”
Section: Acetaldehyde Adsorption By the Selected Carbon-based Adsorbentssupporting
confidence: 88%
See 1 more Smart Citation
“…Therefore, the results demonstrated that ACF 2 outperformed ACF 1 and showed comparatively higher adsorption efficiency than ACF 3 . Similar results were derived in a previous study on cellulose-based ACFs modified by an amine functional group for the adsorption of acetaldehyde under 40% humidity conditions [32]. At start acetaldehyde adsorbed physically onto the active sites with oxygen and nitrogen of adsorbent that creates a bonding with acetaldehyde molecule quickly.…”
Section: Acetaldehyde Adsorption By the Selected Carbon-based Adsorbentssupporting
confidence: 88%
“…The results indicated that the performance of the composite adsorbents in terms of acetaldehyde adsorption from the air was poor under wet conditions. The adsorption efficiencies of the composite materials under wet conditions were lower than those under dry conditions, as mentioned in previous studies [32][33][34]…”
Section: Acetaldehyde Adsorption By Composite Adsorbents Under Dry Ansupporting
confidence: 66%
“…TVSA was expected to lower the desorption temperature, enhance the desorption rate, and shorten the desorption time of heavy VOCs. Pak et al [21] studied the adsorption and desorption of toluene using commercial activated carbons by TVSA. They reported a toluene desorption rate of 90% under the desorption conditions of 90 °C and 13 kPa.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Table 1, studies related to removing VOCs have focused on various aspects, including performance improvement, modeling, performance testing, preparation of adsorbent, modification of adsorbent, and analysis of physicochemical properties. For example, activated carbon was used by Mofidi et al, 19 Dehdashti et al, 20 and Pak and Jeon 21 to discuss its adsorption capacities for styrene and toluene. To obtain more knowledge on the behaviors of the breakthrough curve, the Yoon and Nelson model was applied by Lemus et al 23 and Kalender and Akosman 24 to predict the breakthrough curves for removing chlorinated VOCs.…”
Section: Introductionmentioning
confidence: 99%